Macrophage SR-BI and Atherosclerosis - Tedesco, Vivienne C. (My University, 2006)
The Scavenger Receptor, Class B, Type I (SR-BI) is an integral membrane protein whose expression in the liver is critical to reverse cholesterol transport by mediating the selective uptake of HDL-derived cholesterol. SR-BI is expressed in a variety of tissues including bone marrow derived macrophages and foam cells in atherosclerotic lesions. We have explored the effect of eliminating SR-BI in leukocytes on advanced stages of atherosclerotic plaque development in apoE KO mice. We observed statistically significant cardiomegaly as a result of the elimination of SR-BI in bone marrow derived cells compared to controls (P=0.02). We report that the elimination of SR-BI in bone marrow derived cells in apoE KO mice induced to undergo atherosclerosis by feeding a high fat diet for four weeks leads to no significant difference in cross-sectional atherosclerotic plaque area at the aortic root (4.9±0.9x10^4 μm^2 when SR-BI-/- apoE-/- --> apoE-/- [n=9] and 5.5±0.9x10^4 μm^2 when SR-BI +/+ apoE-/- --> apoE -/- [n=12], P=0.68) or plaque volume through the aortic sinus (1.8±0.3x 10^7 μm^3 when SR-BI-/- apoE-/- --> apoE-/- [n=9] and 1.9±0.3x10^7 μm^3 when SR-BI +/+ apoE-/- --> apoE -/- [n=12], P=0.69). We demonstrate that macrophage SR-BI protein expression can be decreased by cholesterol associated with lipoproteins. Furthermore, we report that in Raw 264.7 macrophage-like cells the expression of SR-BI can also decrease in response to glucosamine treatment. The expression of SR-BI is decreased significantly in cells overexpressing SR-BI (1d1A[mSR-BI] cells [P=0.003]) due to treatment with glucosamine with increased protein mobility. We support this finding by demonstrating that this difference may be the result of altered glycosylation.
Keywords: macrophage, atherosclerosis, Scavenger Receptor, integral membrane protein, tissue